The Role of Green Human Resource Management and Green Leadership in Determining Green Organizational Culture - Mardikaningsih, Rahayu (TIN: Terapan Informatika Nusantara, 2024)
This research examines the role of Green Human Resource Management (GHRM) and Green Leadership (GL) in shaping Green Organizational Culture (GOC) in the Micro and Small Industry (IMK) sector in Surabaya City. Through a quantitative approach with descriptive and explanatory designs, this study reveals that GHRM and GL have a significant influence on the formation of a sustainability-oriented organisational culture. GHRM practices, such as sustainability value-based recruitment and training, and environment-based performance evaluation, support the internalisation of sustainability values among employees. GL contributes through sustainability vision, employee empowerment in environmental initiatives, and encouragement of sustainability innovation. Regression analysis shows that GL and GHRM simultaneously have a statistically significant relationship. These findings reinforce the view that GHRM and GL are strategic pillars in building a green organisational culture, particularly in the IMK sector which faces environmental challenges such as waste and pollution. With effective implementation, GHRM and GL can improve the competitiveness, operational efficiency, and environmental reputation of the IMK sector. This research offers practical insights for businesses to integrate sustainability in their operational strategies.